2022
DOI: 10.1126/science.abq4835
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian oocytes store mRNAs in a mitochondria-associated membraneless compartment

Abstract: Full-grown oocytes are transcriptionally silent and must stably maintain the messenger RNAs (mRNAs) needed for oocyte meiotic maturation and early embryonic development. However, where and how mammalian oocytes store maternal mRNAs is unclear. Here, we report that mammalian oocytes accumulate mRNAs in a mitochondria-associated ribonucleoprotein domain (MARDO). MARDO assembly around mitochondria was promoted by the RNA-binding protein ZAR1 and directed by an increase in mitochondrial membrane potential during o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 106 publications
2
56
0
Order By: Relevance
“…Oocytes lack both an interphase and an S-phase between Meiosis I and II, and they are transcriptionally silent until zygotic genome activation in embryos at the 2-cell stage in mice and 8-cell stage in humans. A recent study reports a mitochondria-dependent mode of mRNA storage in mammalian oocytes in a phase-separated, membraneless region called MARDO important for regulating translation and, consequently, proper embryo development 39 . The common theme of oocytes using membraneless organelles to control RNA storage and localization, and spindle quality 22 points to a mechanism by which cells overcome the challenges of having a large cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Oocytes lack both an interphase and an S-phase between Meiosis I and II, and they are transcriptionally silent until zygotic genome activation in embryos at the 2-cell stage in mice and 8-cell stage in humans. A recent study reports a mitochondria-dependent mode of mRNA storage in mammalian oocytes in a phase-separated, membraneless region called MARDO important for regulating translation and, consequently, proper embryo development 39 . The common theme of oocytes using membraneless organelles to control RNA storage and localization, and spindle quality 22 points to a mechanism by which cells overcome the challenges of having a large cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…In transcriptionally-silent oocytes, the cytoplasm stores maternal mRNAs and ensures spatial and temporal control over the translation and degradation of transcripts synthesized during oogenesis (51). A recent study showed that mammalian oocytes, including humans, dock their maternal mRNA in mitochondria-associated membrane-less domains (52). Anomalous organelle distribution seen in aberrant oocytes is likely to compromise the availability of mRNA and, thus, the efficiency of protein synthesis and post-translation modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed a membraneless compartment storing mRNAs around mitochondria in the germinal vesicle oocyte (Cheng et al, 2022). Combining these evidence, it's likely that RNAs, including those transported from CCs, would aggregate in this compartment if the biosynthesis load is not high.…”
Section: Effects On Oocytes: Meiosismentioning
confidence: 98%
“…Cutting off this RNA transmission can cause impaired oocyte development and a significant reduction in maturation rate, which would confirm our hypothesis. Another study revealed a membraneless compartment storing mRNAs around mitochondria in the germinal vesicle oocyte ( Cheng et al, 2022 ). Combining these evidence, it’s likely that RNAs, including those transported from CCs, would aggregate in this compartment if the biosynthesis load is not high.…”
Section: Functions Of Intercellular Communication In Cocmentioning
confidence: 99%